Evaluating the In-Service Emissions of High-Mileage Dedicated Methanol-Fueled Passenger Cars: Regulated and Unregulated Emissions - Sheng Su; Yunshan Ge; Xin Wang; Mengzhu Zhang; Lijun Hao; Jianwei Tan; Fulu Shi; Dongdong Guo; Zhengjun Yang (Energies, 2020)
This paper reports the regulated, unregulated, and particle number emissions from six high-mileage, China-4 compliant, dedicated methanol taxis over the new European driving cycle. Compared to new vehicles, carbon monoxide, total hydrocarbons, and nitrogen oxides emissions from in-use methanol taxis increased by 76.1%, 40.2%, and 179.8%, respectively. Still, they managed to meet China-4, indicating good in-service conformity. In the test fleet, the test vehicles with longer mileage inclined to emit higher carbon monoxide and total hydrocarbons emissions. Formaldehyde emissions from these field-aged taxis ranged from 1.06 to 2.33 mg/km, which were similar to or lower than those from previously reported pre-Euro-5 gasoline vehicles. One of the six test vehicles produced extraordinarily high unburned methanol emissions, which was about ten times higher than the rest of the properly operating vehicles due to possible misfire, suggesting that unburned methanol will be the primary stress for future methanol applications. Compared to the regulated emissions, formaldehyde and unburned methanol emissions deteriorated at faster rates along with catalyst aging. Particle number emissions from these methanol taxis remained low even after high-mileage driving, suggesting the compatibility of methanol fueling in future particle number compliance.